Efeito da temperatura e de fungicidas na epidemia da mancha-amarela do trigo e no rendimento de grãos - Ranzi, Camila (2015)
The culture of wheat has great importance for Brazil and Rio Grande do Sul Nevertheless, various diseases limit the crop yield in some crops. In no-tillage system, the tan spot caused by Pyrenophor tritici-repentis fungus, anamorphic form Drechslera tritici-repentis cause significant damage to the wheat crop. One epidemic of components, which makes the control of the tan spot, is the expansion of lesions for the production of toxins of the fungus in the plant tissues. In order to learn more about the epidemiology of the disease and improve their management there were conducted researches at UPF, from 2012 to 2014. Initially, wheat plants of Fundacep cultivars Horizonte and or Mirante, inoculated with D. tritici-repentis were subjected to temperatures of 10, 15, 20, 25 and 30 °C and assessed for lesion growth rate and severity. High temperatures (30 °C) caused the highest number, severity and increase of lesions. Then, conidia plates containing agar medium were incubated at the temperatures 0, 5, 10, 15, 20, 25, 30, 35 and 40°C, for 3, 6, 9 and 12 hours for germination evaluation. The maximum germination was obtained at a temperature of 19 ºC and time of 10.6 hours exposure. In order to sporulation, the leaf disks with disease symptoms were incubated in a humid chamber at temperatures of 10, 15, 20, 25 and 30 °C. The highest production of conidia was at 14 °C. In another study, fungicides: propiconazole 125 grams of active ingredient per hectare (g.i.a/ha), azoxystrobin (75 g.i.a/ha), propiconazole + azoxystrobin (125 + 75 g.i.a/ha) and fluxapyroxad + pyraclostrobin (50.1 + 99 9 g.i.a/ha) there were applied 1, 5 and 10 days after inoculation in the cultivars Fundacep Horizonte, Quartz and Iguaçu. In another one, the same fungicides were applied the same 1, 5 and 10 days before inoculation. The propiconazole fungicide showed better efficacy in controlling the tan spot and isolated strobilurin was the least contributed in control. After the fungicide propiconazole (25 g.i.a/ha), azoxystrobin (75 g.i.a/ha) and azoxystrobin + mixture benzovindiflupyr (90 + 45 g.i.a/ha) there were applied in each third of the leaf (lower, medium or higher part) to evaluate the movement of these elements and disease control. The number and size of lesions in the applied third was lower in treatments with propiconazole and azoxystrobin + benzovindiflupyr; only the treatment with propiconazole controlled the tan spot at the site where it was applied and on top of this. Finally, different cultivars were subjected to defoliation levels (flag leaf, two or three leaves above) and the thousand grain weight measured after harvest. Defoliation negatively affected the PMG. As we increased the number of removed leaves from the plant it was decreased the weight of a thousand grains